Effectiveness and quality analysis of methods in studies for the treatment of COVID-19 - Milagre, Selma Terezinha; Pereira, Adriano Alves; de Oliveira Andrade, Adriano; de Andrade Palis, Angélica; Cabral, Ariana Moura; Barreto, Cassiana Gabriela Lima; de Souza, Daniel Baldoino; de Paula Silva, Fernanda; Santos, Fernando Pasquini; Silva, Gabriella Lelis; Guimarães, José Flávio Viana; de Araújo, Laureane Almeida Santiago; et al. (Research on biomedical engineering, 2022)
Purpose COVID-19 has spread and continues to spread rapidly across the world. There is still no approved and effective treatment for the disease. Several drugs are being administered empirically to patients, based on results from studies with limited methodologies. There is an urgent need for systematic reviews to support decision makers and the development of guidelines. The purpose of this paper was to conduct a systematic review of drug studies carried out worldwide for COVID-19, verifying the effectiveness and methodological quality. Method The search for relevant articles was performed in the Cochrane Central, MEDLINE, and Embase databases. The terms and combinations used for the search were ((coronavirus OR “2019-nCoV” OR 2019nCoV OR nCoV2019 OR “nCoV-2019” OR “COVID-19” OR COVID19 OR “HCoV-19” OR HCoV19 OR CoV OR “2019 novel*” OR Ncov OR “n-cov” OR “SARS-CoV-2” OR “SARSCoV-2” OR “SARSCoV2” OR “SARSCoV2” OR SARSCov19 OR “SARS-Cov19” OR “SARS-Cov-19”) OR “severe acute respiratory syndrome*” OR ((corona* OR corono*) AND (virus* OR viral* OR virinae*)) AND ((treatment) OR (medication) OR (symptoms)) AND (drugs)). The review process of the articles was carried out independently by four reviewers using the PRISMA-P method. Results As a result, a total of 30 articles were selected, which addressed the study of one or more medications for severe cases of COVID-19, which were hydroxychloroquine (or chloroquine) and azithromycin, lopinavir/ritonavir, lopinavir/ritonavir, arbidol, and Shufeng Jiedu Capsule, Combinations: remdesivir/lopinavir/homoharringtonine/emetine, remdesivir, interferon, lopinavir and ritonavir, thalidomide/methylprednisolone, tocilizumab, antimicrobial therapy. Conclusion Despite efforts and studies, research does not provide evidence for the use of any drug to treat COVID-19, as the effects, safety, and efficacy are still uncertain. Thus, there is a need for systematic reviews to monitor, synthesize, and update the literature data on the subject, generating reliable evidence for decision makers. COVID-19 should be monitored and the need to develop effective drugs and vaccines to prevent disease progression must be reinforced.